Relationship between oxygen uptake, stroke rate and swimming velocity in competitive swimming - Wakayoshi, K.; D'Acquisto, L. J.; Cappaert, J. M.; Troup, J. P. (International Journal of Sports Medicine, 1995)
Oxygen cost and stroke rate were assessed at various swimming velocities in crawl stroke swimming. Ss were serious trained swimmers but not all of whom specialized in the crawl stroke. Since work in swimming is roughly equivalent to the cube of velocity, relationships were determined using V3 as the measure of velocity. High relationships were revealed. - Oxygen uptake and V3: r = .96 to .998. These relationships were significantly higher than when velocity was expressed as V2 or V. - Stroke rate and V3: r = .93 to .998. When velocity was expressed as V2 the correlation coefficients were lower but not significantly different. However, there was a significant difference when comparisons were made to the correlation coefficients derived from V. Since swimming velocity is determined by stroke rate and stroke length the critical factors in these relationships are stroke rate, oxygen uptake, and stroke length (stroke rate is common to itself and velocity). Changes for the better in any of these factors while the others remain stationary or improve will result in improved performances. It would be incorrect to emphasize one factor and not monitor/consider the others. Implication: Swimming performances are very highly associated with stroke rate, length, and oxygen uptake. Any performance changes that increase the magnitude and efficiency of at least one of these factors, while the others remain constant or also improve, will result in improved performances. However, an overemphasis on one factor coupled with neglect for the other two will likely reduce performances.